Abstract

No abstract available.

Full Article  |  PDF Article

References

  • View by:
  • |
  • |
  • |

  1. R. B. Leighton, R. B. Noyes, G. W. Simon, Astrophys. J. 138, 252 (1962).
  2. J. M. Beckers, Solar Phys. 3, 258 (1968).
    [CrossRef]
  3. W. Bartholomeyczyk, Z. Instrumentenkde 68, 208 (1960).

1968

J. M. Beckers, Solar Phys. 3, 258 (1968).
[CrossRef]

1962

R. B. Leighton, R. B. Noyes, G. W. Simon, Astrophys. J. 138, 252 (1962).

1960

W. Bartholomeyczyk, Z. Instrumentenkde 68, 208 (1960).

Bartholomeyczyk, W.

W. Bartholomeyczyk, Z. Instrumentenkde 68, 208 (1960).

Beckers, J. M.

J. M. Beckers, Solar Phys. 3, 258 (1968).
[CrossRef]

Leighton, R. B.

R. B. Leighton, R. B. Noyes, G. W. Simon, Astrophys. J. 138, 252 (1962).

Noyes, R. B.

R. B. Leighton, R. B. Noyes, G. W. Simon, Astrophys. J. 138, 252 (1962).

Simon, G. W.

R. B. Leighton, R. B. Noyes, G. W. Simon, Astrophys. J. 138, 252 (1962).

Astrophys. J.

R. B. Leighton, R. B. Noyes, G. W. Simon, Astrophys. J. 138, 252 (1962).

Solar Phys.

J. M. Beckers, Solar Phys. 3, 258 (1968).
[CrossRef]

Z. Instrumentenkde

W. Bartholomeyczyk, Z. Instrumentenkde 68, 208 (1960).

Cited By

OSA participates in CrossRef's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Figures (1)

Fig. 1
Fig. 1

The Wollaston prism in convergent light.

Equations (20)

Equations on this page are rendered with MathJax. Learn more.

S 1 o = n o s 1 ;
f 1 o = S 1 o s 1 f = n o f 1 .
S 2 o = S 1 o a ;
f 2 o = f 1 o = n o f 1 .
t 2 o = r 2 / ( 2 S 2 o ) ,
t 2 o = ( r 2 ) / ( 2 S 2 o ) ,
t 2 o = n o n e t 2 o ,
S 2 o = S 2 o n e n o r 2 r 2 .
r 2 / cos 2 α = r 2 / cos 2 β
r 2 r 2 = 4 [ ( n o 2 ) / ( n e 2 ) ] sin 2 α cos 2 α A o .
S 2 o = S 2 o n e n o A o ;
F 2 o = n e A o f 1 .
S 2 o = S 2 o b = A o ( n e S 1 n e n o a ) b .
S 3 o = s 3 o n e [ 1 ( n e 2 1 ) ( n o n e ) 2 n e 2 α 2 ] .
S 3 o = [ A o ( S 1 a n o ) b n e ] [ 1 ( n e 2 1 ) ( n o n e ) 2 n e 2 α 2 ] .
F 3 o = A o [ 1 ( n e 2 1 ) ( n o n e ) 2 n e α 2 ] .
S 3 e = [ A e ( s 1 a n e ) b n o ] [ 1 ( n o 2 1 ) ( n e n o ) 2 n o 2 α ] ; F 3 e = A e [ 1 ( n o 2 1 ) ( n e n o ) 2 n o 2 α 2 ] f 1 .
F 3 o = f 3 e = f 1 ,
S 3 o = s 1 a n o b n e ,
S 3 e = s 1 a n e b n o .

Metrics